LIPID STATUS IN PERIAND POSTMENOPAUSAL WOMEN WITH INSOMNIA - L. I. Kolesnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
We present the results of lipid metabolism evaluation in 23 women during perimenopausal and 36 women during postmenopausal period. We also compared lipid profile in depends on present or absence of insomnia in this patients. We found that lipid profile in postmenopausal women does not depend on sleep disorders. But total cholesterol and cholesterol of low density lipoproteins are different in perimenopausal women.